1982
DOI: 10.1523/jneurosci.02-05-00654.1982
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and behavioral recovery from the effects of spinal cord transection: dependence on metamorphosis in anuran larvae

Abstract: This study of spinal cord injury in bullfrog (Rana catesbeiana) tadpoles using the neuroanatomical tracer horseradish peroxidase (HRP) was undertaken to determine (1) whether the same anatomical regions that normally give rise to ascending or descending spinal tracts do so following complete spinal cord transection and (2) whether the course of behavioral recovery could be related to the anatomical results. The results of this study show that (1) spinal cord continuity is readily restored in tadpoles subjected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 17 publications
6
49
0
Order By: Relevance
“…In the bullfrog, autoradiography experiments indicate that very few descending brain neurons are ''born'' during metamorphosis, and double-label experiments demonstrate that many brainstem neurons that project to the lumbar spinal cord in tadpoles retain this projection as adults (Forehand and Farel, 1982). In the salamander, after transection of the thoracic spinal cord, the percentages of double labeling of descending brain neurons resulting from focal injection of tracers to the spinal cord are 6-27% compared with 3-27% double labeling when both tracers are applied simultaneously (Davis et al, 1989b;Garner et al, 1990).…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…In the bullfrog, autoradiography experiments indicate that very few descending brain neurons are ''born'' during metamorphosis, and double-label experiments demonstrate that many brainstem neurons that project to the lumbar spinal cord in tadpoles retain this projection as adults (Forehand and Farel, 1982). In the salamander, after transection of the thoracic spinal cord, the percentages of double labeling of descending brain neurons resulting from focal injection of tracers to the spinal cord are 6-27% compared with 3-27% double labeling when both tracers are applied simultaneously (Davis et al, 1989b;Garner et al, 1990).…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Studies of spinalized urodele amphibians showed almost complete recovery of function and cord integrity, even in adult stages ( Hibbard, 1963;Piatt, 1955). Anuran tadpoles also have been shown to reconstitute the cord and descending axons after spinal cord transection (Forehand and Farel, 1982;Michel and Reier, 1979). However, adult anurans seem incapable of spinal cord regeneration (Forehand and Farel, 1982;Piatt, 1955), although partial regeneration of the dorsal roots has been documented (Katzenstein and Bohn, 1984; Liuzzi and Lasek, 1985; Liuzzi and Lasek, 1986; Sah and Frank, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…They are thus able to adapt to the state of the retinal axons. These changes were not observed in the case of oligodendrocytes in the spinal cord, where axon regeneration does not occur (Beattie et al, 1990;Forehand and Farel, 1982;Lang et al, 1995).…”
Section: Introductionmentioning
confidence: 83%
“…This occurred at 4 weeks and was unchanged 8 weeks after lesion, except that the gap between the cut ends gradually filled up with GFAP-and fibronectin-positive cells. Thus, in the Xenopus spinal cord where lesioned axons fail to regenerate (Beattie et al, 1990;Forehand and Farel, 1982;Lang et al, 1995), myelin markers in the vicinity of the cut axons persist. 04-expressing glia precursors and radial processes, both of which are present in the optic nerve, are not seen a t the lesion or elsewhere in the cord.…”
Section: Xenopus Glial Cells After Lesion Of the Optic Nerve And Spinmentioning
confidence: 99%